Early Experience with Comaneci, a Newly FDA-Approved Controllable Assist Device for Wide-Necked Intracranial Aneurysm Coiling. (16th November 2020) - Taqi, Muhammad; Raz, Eytan; Vechera, Anastasia; Shapiro, Maksim; Gupta, Rishi; Haynes, Joseph; Taussky, Philipp; Riina, Howard A; Nelson, Peter K; Nossek, Erez Z
Abstract: INTRODUCTION: Wide-necked intracranial aneurysms (WNAs) can be challenging to treat particularly when angioarchitecture carry unfavourable geometries. Balloon-assisted coiling is the workhorse for WNAs, especially when avoiding permanent use of stents. Balloon use comes with flow arrest in the upstream territory thus requiring fast coiling or multiple inflations and deflations to provide intermittent flow restoration. METHODS: We reviewed patients with WNAs that were treated at four institutions between July 2019 and March 2020, using the Comaneci device for coil remodeling of ruptured and unruptured aneurysms. Clinical characteristics, angiographic variables and endovascular results were assessed. RESULTS: A Total of 23 patients were included (16 female). The mean age was 61 (range 44–81) years. Thirteen patients presented with ruptured aneurysms and 10 with unruptured aneurysms. Aneurysms had relative or wide necks; mean neck width was 3.86 mm (range 1.9-6.5 mm) with a mean dome-to-neck ratio of 1.69 mm (range 0.87-3.39 mm). Mean max width was 6.20 mm (range 3.0-9.9 mm). Mean max height was 5.69 mm (range 2.15-11.8 mm). Successful aneurysm occlusion was achieved in 22 of 23 patients. Complete occlusion was achieved in 14 patients, near complete occlusion was observed in 8 patients, and one patient demonstrated residual filling. Mean time of device exposure was 25.3 minutes (range 8–76 minutes). No vasospasm at the device location was observed. In two cases clot formation on the device was noted. There were no clinical sequelae, however, there was one intraprocedural complication which involved the simultaneous use of two Comaneci devices. CONCLUSION: Our initial experience shows that the Comaneci device is a promising and reliable tool that can safely support coil remodeling of WNAs.